Adhesive bonding of thermoplastic polyurethane with metallic wire - Abdullahi, Tijjani; Ahmad, Norhayati; Wahit, Mat Uzir; Harun, Zawati (American Scientific Publishers, 2018)
Steel wires coated with thermoplastic have found a wider range of application in the field of science and engineering. However, steel-polymer interfaces frequently suffer from poor adhesion strength that is undermining their long-term stability under external stress because of weak interaction between the steel and polymer surfaces. Therefore, the present study aims to investigate the influence of adhesive (Chemlok 213 and Cilbond 49SF) on the adhesion strength of galvanized and ungalvanized steel wire coating with thermoplastic polyurethane (TPU). Surface treatments including grinding with sandpaper, thermal oxidation and degreasing with alkaline solution were done on the steel wire substrate prior to coating by compression molding and extrusion process. The adhesion was characterized with a single wire pullout test and field emission scanning microscopy (FESEM). The experimental results confirmed that Cilbond 49SF adhesive with sandpaper grinding treated wire outperformed all other surface treatments tested. In comparison of the processes, compression molding process has an upper hand over the extrusion process because it provide an avenue for sufficient control of curing time required for optimum setting of the adhesive. Thus, this study presents a tailored procedure which can easily fits in to a production line to produce a polymer coated steel wire ropes